MedJet – a new CO2-based disposable cleaning device allows safe and effective bowel cleansing during colonoscopy: a pilot study - Kiesslich, R.; Schuster, N.; Hoffman, A.; Goetz, M.; Galle, P. R.; Santo, E.; Halpern, Z. (Endoscopy, 2012)
Background and study aims: Complete bowel cleansing is mandatory for effective colon cancer screening and surveillance. The aim of the current pilot study, which was conducted in humans, was to test the safety and efficiency of a newly developed disposable cleaning device, the MedJet, for intraprocedural bowel cleansing. Patients and methods: Patients with screening or surveillance colonoscopy after previous polypectomy were included. The colonoscope was first inserted to the cecum and the overall cleansing was assessed according to the Ottawa scale. The MedJet device was used if colon cleansing had been incomplete. The MedJet catheter was passed over the working channel of the colonoscope and the colon was cleaned during withdrawal. The MedJet device delivered controlled jets comprising compressed CO2 and minimal amounts of sterile water, which allowed disintegration and removal of residual stool. The efficiency of cleaning was assessed according to the Boston scale. Results: A total of 32 patients (16 female; mean age 61 years) were treated with the device. No device-related adverse or serious adverse events were noted. MedJet application during withdrawal provided effective and significant improvement in bowel cleansing (P = 0.005). Furthermore, 18 adenomas and 1 colon cancer, which were hidden behind stool remnants, could be identified in 11 patients following use of the MedJet device. However, the withdrawal times were prolonged (11.4±6.0 minutes) due to the additional cleaning procedure. All patients tolerated the procedure well. Conclusions: The new MedJet device enabled highly effective and safe bowel cleansing during colonoscopy. The catheter-based system was easy to use and CO2 was applied for cleansing. The procedure was well tolerated by patients.